AStrategy to enhance Eu3+ emission from LiYF4:Eu nanophosphors and green-to-orange multicolor tunable, transparent nanophosphor-polymer composites - Kim, Su Yeon; Won, Yu-Ho; Jang, Ho Seong (NATURE PUBLISHING GROUP, 2015)
LiYF4:Eu nanophosphors with a single tetragonal phase are synthesized, and various strategies to enhance the Eu3+ emission from the nanophosphors are investigated. The optimized Eu3+ concentration is 35 mol%, and the red emission peaks due to the D-5(0)-> F-7(J) (J=1 and 2) transitions of Eu3+ ions are further enhanced by energy transfer from a sensitizer pair of Ce3+ and Tb3+. The triple doping of Ce, Tb, and Eu into the LiYF4 host more effectively enhances the Eu3+ emission than the core/ shell strategies of LiYF4:Eu(35%)/LiYF4:Ce(15%), Tb(15%) and LiYF4:Ce(15%), Tb(15%)/LiYF4: Eu(35%) architectures. Efficient energy transfer from Ce3+ to Eu3+ through Tb3+ results in three times higher Eu3+ emission intensity from LiYF4:Ce(15%), Tb(15%), Eu(1%) nanophosphors compared with LiYF4:Eu(35%), which contains the optimized Eu3+ concentration. Owing to the energy transfer of Ce3+ -> Tb3+ and Ce3+ -> Tb3+ -> Eu3+, intense green and red emission peaks are observed from LiYF4:Ce(13%), Tb(14%), Eu(1-5%) (LiYF4:Ce, Tb, Eu) nanophosphors, and the intensity ratio of green to red emission is controlled by adjusting the Eu3+ concentration. With increasing Eu3+ concentration, the LiYF4:Ce, Tb, Eu nanophosphors exhibit multicolor emission from green to orange. In addition, the successful incorporation of LiYF4:Ce, Tb, Eu nanophosphors into polydimethylsiloxane (PDMS) facilitates the preparation of highly transparent nanophosphor-PDMS composites that present excellent multicolor tunability.
Keywords: ENERGY-TRANSFER; FACILE SYNTHESIS; DOPED LIYF4; CONVERSION; NANOCRYSTALS; LUMINESCENCE; PHOSPHORS; PHOTOLUMINESCENCE; PHASE; CE3+